Survey of Occupational Therapy Students' Attitudes, Knowledge and Preparedness for Treating LGBT Clients - Deborah J. Bolding; Vivian Rodriguez; Helen Nguyen; Laurie A. Drabble (Journal of Occupational Therapy Education, 2020)
Members of lesbian, gay, bisexual and transsexual (LGBT) populations are sexual and gender minorities and are at risk for significant health disparities compared to heterosexual populations. This study examined occupational therapy students’ and recent graduates’ (n=435) basic knowledge, clinical preparedness and attitudinal awareness for working with LGBT clients using the Lesbian, Gay, Bisexual, and Transgender Development of Clinical Skills Scale (LGBT-DOCSS; Bidell, 2017). Students in the study generally rated themselves low (between three and four on a seven-point scale) on questions related to clinical preparedness, indicating they felt they did not have adequate training relative to working with LGBT clients. Both basic knowledge and clinical preparedness for working with LGBT populations was positively influenced by hours of curriculum content related to sexual minority populations. However, 21% (n=91) of participants reported the topic was not covered in the curriculum, while an additional 68% (n=295) reported less than two hours of time developed to LGBT topics. It is suggested that education focus on terminology, health disparities, an examination of personal and societal attitudes that affect outcomes, important health and psychosocial needs, culturally sensitive communication, creating inclusive practice setting and clinical practice and communication unique to this population.